An Analysis of Phonological Stylistic Repetition in Slogans of International Products Marketed in Indonesia - Perwira, Yanuarria Kukuh (PAROLE: Journal of Linguistics and Education, 2023)
The slogan creation process has always been a scourge for product manufacturers since they need to make something that is concise while being able to catch the consumers’ attention. One of the most used methods in creating slogans is by utilizing stylistic linguistics. This paper focuses on phonological aspects of repetition used in slogans of international brands marketed in Indonesia, and compares both the original and the Indonesian versions of the slogans. Out of 432 slogans gathered, the analysis results revealed that the most used style in both languages is rhyming. On the other hand, the least used are epiphora and epizeuxis. The domination of rhyming style usage in both languages is influenced by cultural history, especially in literary artworks. Although rhyming dominates the type of stylistic used in creating slogans, the percentage of slogans using phonological stylistic repetitions is quite low. In the original version, the percentage of slogans using phonological stylistic repetition is only 17.13%. Meanwhile, the Indonesian counterpart only shows 17.82% of phonological stylistic repetition.